Peran Nilai-Nilai Koperasi Bagi Keberlanjutan Usaha Pada Komunitas Batik Citra Gendhis Kabupaten Malang - Nunuk Suryanti; Fitriani Fitriani; Akhmad Suyono; Purba Andy Wijaya (UIR Press, 2022)
Cooperatives are one of the people's economic forums. The form of economic democracy in Article 33 of the 1945 Constitution is cooperative. The purpose of this study is to find out how the role of cooperative values in providing an impact on the business sustainability of MSME actors. The type of research used is qualitative research with a case study approach. Data collection techniques in the form of in-depth interviews, observations, and FGDs. The data analysis technique used the Miles and Huberman model, with the NVIVO 12 program. The results showed that the cooperative values in the batik community were beneficial for members in obtaining capital and ease of production and marketing.